Quality assessment of lettuce (Lactuca sativa L.) grown in different hydroponic systems in Iloilo. - Fuentespina, Ida Anne Cacharel O.
Hydroponics, an eco-friendly soil-less farming method, is widely used for lettuce cultivation due to its resource-efficient nature. However, upholding quality and food safety remains paramount. This study evaluated Lalique lettuce (Lactuca sativa L.) grown from different hydroponic greenhouses across Iloilo by comparing their microbial, physico-chemical, and sensory qualities. Samples from Locations A and C were grown using the Kratky Method, while Location B used the Nutrient Film Technique (NFT). Location A, which had the highest microbial load (TNTC), highest total coliform count (6.17 x104 cfu/g) and was the only sample detected with E. coli. Location C had the lowest microbial load with an average of 1.96 x104 cfu/g, while Location B had the lowest total coliform count with an average of 2.16 x103 cfu/g. There was no significant difference in the total microbial load, E.coli and total coliform count of samples (P = 0.05). Lettuce samples were generally regarded as safe to eat. Although specific microbial standards in the Philippines for E. coli and total coliform of fresh produce are lacking, food safety measures are recommended to mitigate potential foodborne illnesses. Sensory assessments through Triangle Tests exhibited no distinguishable difference among samples (α = 0.05). Descriptive analysis showed the lettuce samples to be generally fresh, slightly bitter, with opaque leaves and minimal damage. Panelists perceived the color of lettuce samples to be "Lime Green" and "Titanite" based on the Pantone color reference provided during evaluation. The physico-chemical attributes namely, pH (6.03-6.36), water activity (0.99), moisture content (88.86%-93.28%) and titratable acidity (% malic acid) (0.14-0.22) did not display significant differences among samples and were within ranges comparable to literature. In conclusion, this study demonstrates that the chosen hydroponic system has no significant difference in the lettuce quality in terms of its microbiological, physico-chemical, and sensorial characteristics.